Inhibition of A2AR alleviates adenosine-mediated suppression of plasma cell differentiation - Tieppo, Paola; Shehade, Hussein; Martinoli, Chiara; Mercier, Marjorie; Carbonez, David; Rosewick, Nicolas; Jung, Sophie; Vezzu, Anais; Pirlot, Boris; Wald, Noemie; Ma, Stephanie; Chaible, Lucas; et al. (Frontiers in Immunology, 2025)
IntroductionHigh levels of extracellular adenosine, highly abundant in the tumor microenvironment, promote immune suppression mainly through the A2AR expressed by tumor-infiltrating immune cells. Given the importance of tumor-infiltrating B and plasma cells (PCs) in antitumor responses, we investigated the effect of A2AR on human B cells.MethodsWe performed quantitative mass spectrometry imaging followed by GeoMx analysis on 10 tumor samples. Immunohistochemistry, multiplex immunofluorescence and scRNA-seq were used to assess A2AR expression on tumor and tonsillar B cells. In vitro differentiated B cells and sorted tonsillar B cells were stimulated in the presence of the A2AR agonist CGS-21680 with or without the A2AR antagonist inupadenant, and analysed by flow cytometry, LegendPLEX and scRNA-seq. The in vivo effect of inupadenant was assessed using Visium on tumor biopsies from five cancer patients. ResultsThe frequency of PCs was the most negatively affected by adenosine among the immune cells present in the tumor microenvironment. Furthermore, both tonsillar and tumor-associated B cells, including germinal center (GC)-like B cells, PCs and plasma blasts, collectively referred to as antibody-secreting cells (ASCs), expressed high levels of A2AR. Triggering of A2AR inhibited B cell maturation into ASCs and immunoglobulin production in vitro, and impaired upregulation of PC genes upon stimulation. These effects were restored by inupadenant (EOS100850), a potent and highly selective small molecule A2AR antagonist. Spatial transcriptomics analysis of tumor biopsies from patients treated with inupadenant revealed that ASCs specifically increased in tertiary lymphoid structures. DiscussionAltogether, these data demonstrate that A2AR plays a key role in adenosine-mediated inhibition of B cell maturation toward ASCs through a B cell-intrinsic mechanism, and that this effect is fully reverted by inupadenant.